Avaliação de impacto do Programa de Modernização Tributária e da Gestão dos Setores Sociais Básicos (PMAT) na arrecadação de ISSQN e IPTU dos municípios, no período de 1999 a 2011 - Oliveira, Robson Eneas de (2015)
The aim of this research is to evaluate the impact of Tributary Administration Modernization Program (PMAT), provided by the Brazilian Development Bank (BNDES), in the trajectory of tax revenue of municipalities, from 1999 to 2011. In this regard, we used a panel data model with fixed effects controls. The dependent variables are ISSQN (Any Nature Service Tax) and IPTU (Real State Tax) and the explanatory variables are the desegregated GDP of Municipalities and the BNDES disbursements. The regressions were performed with treatment dummies and with the log transformation of BNDES disbursements, separately. Despite the use of entire sample of control group to run the regressions, we define two subsamples to try to avoid the risk of selection bias. The first delimitation of control group are the municipalities that tried to get the BNDES funding, but did not get it. The second control group are the municipalities that are geographically close to those that received the funding. The results indicated that, in most regressions, there is no statistical relationship between the PMAT and the trajectory of tax revenue of municipalities. Just in the regressions performed with the control group that tried to get the BNDES’s funding (but did not get it), it was found that there is statistical relevance concerning IPTU, at significance level of 5%.